STUDI POTENSI PEMANFAATAN LIMBAH SERAT BATOK SIWALAN (BORASSUS FLABELLIFER L) SEBAGAI BAHAN BAKU KERAJINAN LOKAL (BENANG) GRESIK - Admin APERTI (JURNAL TEKNOLOGIA, 2018)
Siwalan have latin name as Botassus Flabellifer L. Type of flora which widely spread in eastern Indonesia such as Nusa Tenggara Timur, Nusa Tenggara Barat, Southern Sulawesi, Bali, and East Java. Siwalan has become one of local icon in Gresik (East Java) which is processed into traditional beverage “legen”, its leaves as food packaging, and its fruit/ental become snack. Making it as a beverage and local cuisine traded as well as a livelihood object of the population. One siwalan seller is usually processed 500-1000 pieces of fruit within a maximum period of five days. By observing both social and environmental indications, it can now be assumed that there is enough availability of siwalan in Gresik, siwalan as a food commodity, and limited research of handycraft design, and the waste of siwalan shell. If the was siwalan waste is decomposed, then it can be found fiber which has lengthwise physical properties. Fiber can be processed into yarn through spinning and become raw material of handicraft. Hence, to complete the research it needs practical research approaching process which includes qualitative, quantitative, and experimental, so that the purpose of the research which is to enhance the material of siwalan shell and to produce variant yarn will be achieved. And therefore, through such process, the advantages of the research are not only to open the siwalan fiber as an alternative option as raw material of handicraft, but it can also be taken as references by craftsmen as business with local wisdom.